Historical and metallurgraphic study of equipment fromsnmrtin’s army - Silvana Carrizo, Patricia (2011)
The following article proposes an interdisciplinary study in which the Argentinian history, the archeology and the engineering are met. The study has as protagonists, two pieces of cooper that belong to the San Martin’s campaign and are the heritage of the Casona Santa Rosa de Lujan de Cuyo Americanist Regional Museum, located in Mendoza Argentine. Unfortunately it is not known its precedence or the reservoir where they were found, and that is why we cannot affirm, however, it can be said that it is very possible that they could have belonged to the army of San Martin General, as trough the investigation of some characteristics of its origin and the establishment of a relative chronology for these objects, and using the characteristics of its fabrication methods with these data, we were able to assign these pieces in the line of history, as well as confirming it, and for this it can be affirmed that it is very probable its belonging to the equipment fabricated by Fray Luis Beltran, for the San Martin’s army. For this research, it was used historical sources, metallurgic and chemical data from laboratory studies.